2010
DOI: 10.1007/s11666-009-9467-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Process and Coating Reliability Through Monitoring of Process and Design Relevant Coating Properties

Abstract: Thermal spray in general, plasma spray in particular, is a highly complex process with numerous interacting variables associated with generation of the spray stream, deposit formation dynamics, and the resultant property linkages. Compounding this variability further are both the spatial (different booths and different locations) and temporal (process start-stops, hardware degradation, operator etc.) effects. As such, an understanding of process and coating consistency and variability offers significant challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 36 publications
0
25
0
1
Order By: Relevance
“…Son multitud los trabajos que han estudiado la influencia de los parámetros de la proyección por plasma en las características del recubrimiento final (7)(8)(9). Desde hace ya bastantes años, se dispone de equipamiento que permite monitorizar el comportamiento que experimenta el material en el interior del plasma (10). Estos equipos se han utilizado para conocer la influencia que ejercen los parámetros de proyección en la velocidad y temperatura de las partículas en el interior del plasma.…”
Section: Diagnóstico Del Comportamiento De Los Polvos En El Vuelounclassified
“…Son multitud los trabajos que han estudiado la influencia de los parámetros de la proyección por plasma en las características del recubrimiento final (7)(8)(9). Desde hace ya bastantes años, se dispone de equipamiento que permite monitorizar el comportamiento que experimenta el material en el interior del plasma (10). Estos equipos se han utilizado para conocer la influencia que ejercen los parámetros de proyección en la velocidad y temperatura de las partículas en el interior del plasma.…”
Section: Diagnóstico Del Comportamiento De Los Polvos En El Vuelounclassified
“…Although many reports which associated with the effect of microstructure on the properties of as-sprayed coatings can be found [12][13][14][15], the detailed information on the relationship between particle in-flight behavior, defect and mechanical properties of YSZ coatings is still scarce. In view of the above, the correlation between particle in-flight behavior and coating defects was established and the influence of defects on the mechanical properties of assprayed coatings was further studied.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity of monoclinic zirconia is higher than the tetragonal and cubic phases [11][12][13] . Some studies investigated the relationship between the spray process and the microstructure of the thermal barrier coating 14,15 . It was found that with increasing particle velocity and temperature the coating is densified and the thermal conductivity increases 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies investigated the relationship between the spray process and the microstructure of the thermal barrier coating 14,15 . It was found that with increasing particle velocity and temperature the coating is densified and the thermal conductivity increases 14,15 . The quantitative effect of grain boundaries on the thermal conductivity was analyzed which shows that the thermal conductivity of small grains is lower compared to large grains [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%